2020
DOI: 10.34084/bshr.728865
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Covid 19 Pandemic on the Number and Method of Birth in the 3rd Stage Pandemic Hospital in our Region

Abstract: ÖzetAmaç COVID-19 pandemisi sırasında dünyanın bazı bölgelerindeki karantina uygulamaları, toplumsal izolasyon ve sosyal mesafe gibi önlemler hayatımızdaki pek çok tercihimizi etkilediği gibi gebelerin bu dönemde takip ve doğum için hastane seçimlerini de etkileyebilir. Çalışmamızda; pandemi dönemi ile bir önceki yıl aynı zaman aralığı karşılaştırılarak bu değişimin belirlenmesi amaçlanmıştır Materyal ve MetodÇalışmamız retrospektif ve kesitsel olarak bölgemizde pandemi hastanesi olarak seçilen Karabük Ünivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In a recent review, Jamieson et al 15 reported a prevalence of COVID-19 ranging from 3-20% . Mutlu et al 16 reported that the total number of births and vaginal birth rates decreased in the first wave in a tertiary hospital in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Jamieson et al 15 reported a prevalence of COVID-19 ranging from 3-20% . Mutlu et al 16 reported that the total number of births and vaginal birth rates decreased in the first wave in a tertiary hospital in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been reported that pregnant women want to start childbirth early or give birth by cesarean section due to the anxiety and stress they experience (23). It was argued that during the COVID-19 pandemic period, some pregnant women take precautions to protect themselves and their babies from this infection, which has a potential of mortality and a high risk of transmission (36).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that these conditions have a similar rationale, studies have also shown that pregnant women with concerns about being infected with COVID-19 prefer private medical institutions and cesarean section deliveries, which they find safer in terms of the risk of transmission at childbirth, so the number of vaginal births decreases (36,37). This may lead to maternal and fetal health risks that pregnant women may face due to surgery when trying to avoid danger, as well as worsening the course of the disease in case of transmission (37).…”
Section: Discussionmentioning
confidence: 99%
“…Pandemi hastanelerinde yapılması planlanan doğumlar, doğum sırasında bulaş riski açısından kaygı oluşturmaktadır. Bu sebeple gebelerin doğumlarını, kendilerini daha güvende hissedebilecekleri pandemi hastanesi dışında ve özel hastanelerde yapmayı tercih ettikleri bildirilmiştir (Mutlu, 2020). Ayrıca gebelerin pandemi öncesinde bir doğum planı varken pandemideki kısıtlamalar nedeniyle doğumda yanlarında olacak kişilerin bulunmayışı ve doğum planlarının değişmesi konusunda kaygılandığı belirtilmektedir (Aydın ve ark., 2020;Brooks ve ark., 2020).…”
Section: Covid-19 Pandemisi Sürecinde Gebelerin Psikososyal Sorunlarıunclassified